The Relevance Between Javanese Pitutur Luhur and Islam Religiosity - Riky Zakub; Sahid Teguh Widodo; Budhi Setiawan (IBDA` : Jurnal Kajian Islam dan Budaya, 2018)
Javanese pitutur luhur is an honorable thought as the inheritance from Javanese ancestors in which it is bequeathed from generation to generation. Pitutur luhur is led as guidance for Javanese societies throughout their life. It contains the ancestors’ thoughts about some aspects of life since every human being (including Javanese people) has guidance for life. As religious people, for Muslim societies, it is a must to bring Qur’an and hadith into their guidance of life. This study discusses the relevance between Javanese Pitutur luhur and Islamic religiosity based on Qur’an and hadith. The result of this study shows that there is harmony and relevance between Javanese Pitutur luhur and Islam religiosity as explained in Qur’an and Hadith. To sum up, both of them can be equal to the guidance of life, and to provide directions in the middle of deculturation, dereligiosity, paganism, and secularism towards religious and cultural values.